DINAMIKA PENGEMBANGAN OBYEK WISATA GREEN KAYEN KALURAHAN CONDONGCATUR KAPANEWON DEPOK KABUPATEN SLEMAN - Kurniawati, Dwi; Sugiyanto, Sugiyanto (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
Green Kayen is a pioneering tourist village located in Padukuhan Kayen, Condongcatur Village, Kapanewon Depok, Sleman Regency, Special Region of Yogyakarta. Kayen consists of forests, rivers and dams on Village Treasury Land (TKD). The aim of this research is to determine the dynamics of the development of the Green Kayen tourist attraction in Condongcatur Village, Kapanewon Depok, Sleman Regency and the factors that hinder the development of the Green Kayen tourist attraction in Condongcatur Village, Kapanewon Depok, Sleman Regency. This research is research with a qualitative descriptive research method. Data collection techniques are carried out through observation, interviews and documentation. The indicators in this research use Cooper's theory in Sugiyanto (2020: 114) that there are 4As that a tourist attraction must have, namely attraction, accessibility, amenities and ancillary service. The results of the research show that the dynamics of the development of the Green Kayen tourist attraction in Condongcatur Village, Kapenewon Depok, Sleman Regency from 2016 to 2023 are not considered optimal. This is because the development of tourist attractions carried out by POKDARWIS Green Kayen only started in 2020 and only focuses on developing Amenity indicators, while other indicators such as Attraction, Accessibility and Ancillary Service have been developed but are still minimal. Factors inhibiting the development of the Green Kayen tourist attraction in Condongcatur Village, Kapenewon Depok, Sleman Regency consist of land legality, limited funds, no directional signs, narrow road conditions, difficult administration and reporting processes, no site plan yet, human resource problems, and there is no cooperation with disaster management organization.Keyword: Development dynamics; tourist attraction; and Green Kayen.